Maitland in chronic lumbar pain of young adults improves pain and functionality - Ferreira, Marcela da Gama e Silva; Mèlo, Luiz Carlos de; Mendonça, Horianna Cristina Silva de; Cabral, Kryslly Danielle de Amorim; Rodrigues, François Talles Medeiros; Nascimento, Lívia Shirahige Gomes do; Guerino, Marcelo Renato; Ferreira, Ana Paula de Lima; Araújo, Maria das Graças Rodrigues de (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Back pain is an injury to health that accompanies humans since the beginning of time. The pain in the column are recurrent complaints of the physical therapy students of the Universidade Federal de Pernambuco. Objective: The objective was to verify the effectiveness of the Maitland Method, to reduce pain and to improve the functionality of physical therapy students. Methods: 12 volunteers were analyzed in this study, four were allocated in the Intervention Group (IG) and eight in the Control Group (CG). They were evaluated for anthropometry, flexibility (finger-ground index), functionality (Roland Morris Questionnaire-QRM), pain level (Visual Analogue Scale-EVA), and perception of patient improvement. Results: In the QRM scores, it was observed that the CG showed a significant improvement over the initial evaluation in both the T1 (p= 0.026) and the T2 (p= 0.018) reevaluation. The same was observed in VAS in relation to T1 (p= 0.018) and T2 (p= 0.017). IG remained constant throughout the treatment. Conclusion: We can infer that both the Maitland Method and the exercises are effective for the reduction of pain and improvement of function in individuals with chronic low back pain.